The person-organization fit of warehouse operations employees. - Autry, Chad W. (My University, 2001)
Warehouse operations employees from seven firms were surveyed regarding their person-organization fit perceptions, status traits, job attitudes, and coping behaviors. Regression results indicate that person-organization fit is positively associated with control-type coping behaviors, and negatively associated with escape-type coping behaviors. Additionally, partial support was found for the presence of the status trait moderator effect.

The current research proposes that high turnover rates, as well as other constructive (control) and/or destructive (escape) warehouse employee workplace behavioral responses, are the result of stress caused by lack of fit between employee job expectations and the realities found in the warehouse or distribution center. Thus, there are two primary objectives of this dissertation. The first objective is to assess the relationships between person-organization fit and potential coping responses. The second objective is to determine whether the ascribed or achieved nature of a status trait attributed as the stressor moderates the person-organization fit---coping response relationship.

Record low levels of unemployment characterized the economically prosperous period of the mid-to-late 1990's. During this period, warehouses and distribution centers in the United States experienced extremely high turnover rates, as workers accepted less taxing and more glamorous positions that became available in other industries. Turnover among warehouse operations employees has since reached crisis levels, and is responsible for a significant portion of human resource costs.
Keywords: Business Administration, Marketing.; Warehouses United States Employees Job satisfaction.; Adjustment (Psychology); Psychology, Industrial.